Continental Drift: The Canadian Clubs of New York City and the Question of Canadian–American Relations, 1885–1914 - Woodsworth, Michael (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2011)
The three decades leading up to World War I witnessed major shifts in the diplomatic relationship between Canada and the United States. Though attempts to forge a North American free-trade agreement failed, Canada and the U.S. forged unprecedented bilateral ties. This article examines how Canadian expatriates in the United States between 1885 and 1914 perceived the changing relationship between their native land and their adopted home. It focuses on the Canadian clubs of New York City, which provided a space in which well-to-do immigrants fostered Canadian patriotism, cultivated ties with politicians, and debated the Dominion’s future with leading intellectuals and diplomats. These clubs, it is argued, articulated a new brand of Canadian nationalism deeply rooted in North America. At times this vision matched sentiments north of the border; at others, it inflamed them. Most notably, during the 1891 and 1911 federal elections, New York’s Canadians campaigned fervently for free trade, and in so doing found themselves at odds with a majority of Canadians north of the border.